The Role of E-Performance Appraisal Information System on Teacher Performance - Okoye, Anthony Ekene; Njeje, Doreen; Kiflemariam, Abraham (African Journal of Education and Practice, 2025)
Purpose: The study examined the role of e-performance appraisal information system on teacher performance. Methodology: The study depended on quantitative data based on formatted questionnaires. The target population for this study consisted of the teachers at all Catholic secondary schools within the Onitsha Archdiocese of Nigeria, totaling 36 schools. Descriptive research design was used in this study. This study employed a stratified random sampling technique to choose the participants. To guarantee the validity of the data collection tools, the pilot test was carried out using 11 respondents. Inferential analysis was used to ascertain whether there was a relationship between E-Performance Appraisal Information System and teacher performance. Findings: The findings of the study were E-Performance Appraisal Information System (EPAIS) has a substantial correlation with the performance of teachers (r =.400, p < 0.05). There is a consensus regarding the positive influence of E-Performance Appraisal Information Systems on teacher performance. Unique Contribution to Theory, Practice and Policy: To enhance the performance of E-Performance Appraisal Information Systems, the study recommended inclusion of dynamic capabilities that make it possible for the system to evolve in accordance with organizational priorities as well as teachers' needs.